Innovation becoming trajectories: leveraging lateral and vertical moves for collaborative diffusion of twenty-first century learning practices. Issue 4 (2nd October 2017) - Hung, David; Toh, Yancy; Jamaludin, Azilawati; So, Hyo-Jeong
Abstract: This paper argues for innovation diffusion as a "becoming" process in the context of lateral and vertical moves. The context of these innovations involves technology-mediated innovations and their diffusion trajectories in the Singapore education system. Embedded in a centralized-decentralized dialectics, this paper traces particular innovations from their nascent beginnings to their present state of play. We found that the cases we observed had lateral (or decentralized) moves and were subsequently supported by vertical (or centralized) ones. Characterizing these innovation diffusions was challenging as we found them to move across models according to different granularities and levels of analysis. Instead, we have chosen to characterize these diffusion patterns as "innovation becoming". We attempt to distil some substantive generalizations from three case studies presented and how decisions can be made for future innovation diffusions. We recognize that the trajectory for innovation diffusion is inextricably linked to the identity projected by the particular innovation and the leadership supporting it.